Modification of polysulfone ultrafiltration membranes with PVA and TiO2 for better antifouling - Thanh Phong, Mai; Xuan Thang, Cao; Dinh Tuan, Phan (Vietnam Journal of Science and Technology, 2017)
The objective of this study was to investigate anti-fouling property of modified polysulfone ultrafiltration (UF) membranes. Polysulfone UF membranes were modified by coating a thin film of polyvinyl alcohol (PVA), or a mixture of polyvinyl alcohol and titanium dioxide (TiO2) on surface. Effects of curing temperature on the coated membranes were also studied. The modified membranes were tested with 0.5 g/L sodium alginate solution and industrial dye wastewater. Curing temperature influenced remarkably flux and fouling property of the membranes. Among experiments studied, 85 oC was the best curing temperature. The PVA and PVA/TiO2-coated membranes reduced fouling significantly. Dispersion of TiO2 nanoparticles on membrane surface improved considerably bacteria removal of the membranes.